Pengembangan Ar (Augmented Reality) Melalui Poster Digital Tentang Eksplorasi Karier Siswa SMA Negeri 2 Tambang - Gladis Zulita Safitri; Elni Yakub; Dian Oktary (Jurnal Ilmiah Dikdaya, 2026)
Career exploration plays an important role in helping students determine the direction of their future education and career choices. This study aims to develop Augmented Reality (AR)-based career guidance media through digital posters as an interactive tool to increase student engagement in the career exploration process. The study uses the Research and Development model ADDIE on tenth-grade students. The resulting product was deemed highly valid by media and material experts and highly practical based on trials by students and guidance counselors. Thus, this AR media is suitable for use as an alternative career service medium. The contribution of this research lies in the innovation of using AR in guidance and counseling services to support the strengthening of student career exploration